Enhancement of Bacillus thuringiensis Cry1Ab and Cry1Fa Toxicity to Spodoptera frugiperda by Domain III Mutations Indicates There Are Two Limiting Steps in Toxicity as Defined by Receptor Binding and Protein Stability - Gómez, Isabel (Appl Environ Microbiol, 2018)
Bacillus thuringiensis Cry1Ab and Cry1Fa toxins are environmentally safe insecticides that control important insect pests. Spodoptera frugiperda is an important maize pest that shows low susceptibility to Cry1A toxins, in contrast to Cry1Fa, which is highly active against this pest and is used in transgenic maize for S. frugiperda control. The β16 region from domain III of Cry1Ab has been shown to be involved in interactions with receptors such as alkaline phosphatase (ALP) or aminopeptidase (APN) in different lepidopteran insects. Alanine-scanning mutagenesis of amino acids of Cry1Ab β16 ((509)STLRVN(514)) revealed that certain β16 mutations, such as N514A, resulted in increased toxicity of Cry1Ab for S. frugiperda without affecting the toxicity for other lepidopteran larvae, such as Manduca sexta larvae. Exhaustive mutagenesis of N514 was performed, showing that the Cry1Ab N514F, N514H, N514K, N514L, N514Q, and N514S mutations increased the toxicity toward S. frugiperda. A corresponding mutation was constructed in Cry1Fa (N507A). Toxicity assays of wild-type and mutant toxins (Cry1Ab, Cry1AbN514A, Cry1AbN514F, Cry1Fa, and Cry1FaN507A) against four S. frugiperda populations from Mexico and one from Brazil revealed that Cry1AbN514A and Cry1FaN507A consistently showed 3- to 18-fold increased toxicity against four of five S. frugiperda populations. In contrast, Cry1AbN514F showed increased toxicity in only two of the S. frugiperda populations analyzed. The mutants Cry1AbN514A and Cry1AbN514F showed greater stability to midgut protease treatment. In addition, binding analysis of the Cry1Ab mutants showed that the increased toxicity correlated with increased binding to brush border membrane vesicles and increased binding affinity for S. frugiperda ALP, APN, and cadherin receptors. IMPORTANCE Spodoptera frugiperda is the main maize pest in South and North America and also is an invasive pest in different African countries. However, it is poorly controlled by Bacillus thuringiensis Cry1A toxins expressed in transgenic crops, which effectively control other lepidopteran pests. In contrast, maize expressing Cry1Fa is effective in the control of S. frugiperda, although its effectiveness is being lost due to resistance evolution. Some of the Cry1Ab domain III mutants characterized here show enhanced toxicity for S. frugiperda without loss of toxicity to Manduca sexta. Thus, these Cry1Ab mutants could provide useful engineered toxins that, along with other Cry toxins, would be useful for developing transgenic maize expressing stacked proteins for the effective control of S. frugiperda and other lepidopteran pests in the field.